PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL - Azhar, Akbarurrizqillah Al; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to test the influence of local own resource revenue (PAD), general allocation fund (DAU), and special allocation fund (DAK) to the capital expenditure of Districts / cities government in East Java. The population of this research is all districts / cities in East Java Province in 2012-2015 periods. The purposive sampling method has been conducted by using 139 the Realization Report of Revenue Budget and Local Government Expenditure (LRA-APBD) from 29 local district governments and 9 cities governments in East Java province during the 2012-2015 fiscal periods. The result of this research is multiple linear regressions analysis technique explains that Partially 1) local own source revenue give significant and positive influence to the allocation of capital expenditure. 2) general allocation fund give significant and positive influence to the allocation of capital expenditure. 3) special allocation fund give significant and positive influence to the allocation of capital expenditure. And simultaneously the local own source revenue, general allocation fund and special allocation fund give significant and positive influence to the allocation of capital expenditure of districts / cities in East java. The value of Adjusted R Square is 0.948, it shows that the independent variables can explain the dependent variable.Keywords: Local own source revenue, general allocation fund, special allocation fund, capital expenditure.